New genomic techniques and their European Union reform. Potential policy changes and their implications - Zimny, Tomasz (Frontiers in Bioengineering and Biotechnology, 2022)
The article discusses amendment options (no significant change, lowering of administrative burdens or exemption of certain products from the legislation) for the European Union (EU) authorization procedures of New Genomic Techniques’ (NGT) products and their consequences for the sector and research institutions, particularly in the context of internal functioning, placing products on the market and international trade. A reform of the EU regulatory system requires a change in the procedures for the authorization of NGT products, otherwise EU researchers and investors may still be at a competitive disadvantage (as compared to Argentina, Brazil, Canada, USA or the UK) due to the inefficiency of the current system and the committee procedure for authorization. New legislation, currently being adopted in the UK. is also presented for comparison.